The Effect of Adding Propolis to Formula Milk on The Streptococcus Sobrinus Inhibition Zone (In Vitro) - Welly Anggarani; Adisty Restu Poetri; Dinda Nabila Alfani (Denta Journal Kedokteran Gigi, 2024)
Background: Caries is one of the dental and oral health problems that are often suffered by children. One of the main causes is the habit of children consuming formula milk as it contains sucrose. Streptococcus sobrinus is an oral pathogenic bacteria that has a role in the initial process of dental caries. One of the natural ingredients that function as anti-caries is propolis. Objective: Therefore, this study aims to determine the effect of adding propolis to formula milk on the inhibition zone of Streptococcus sobrinus bacteria. Methods: This type of research is a Laboratory Experiment with a Post-Test control Group Design. It consists of 4 groups, namely the formula milk group without propolis as a negative control, the formula milk treatment group with propolis concentrations of 5%, 10%, and 20% carried out with 7 replications of each group. The sample is a pure isolate of Streptococcus sobrinus bacteria. Results: The results showed the average inhibition zone was the formula milk group without propolis was 0.00±0.00 mm, the formula milk group with propolis concentration of 5% was 12.87±1.18 mm, the formula milk group with propolis concentration of 10% was 16.65±1.51 mm, and the formula milk group with propolis concentration of 20% was 24.87±0.39 mm. Conclusion: It means the addition of propolis to formula milk has been proven to be effective in inhibiting the growth of Streptococcus sobrinus bacteria.